Use of and access to health services in Brazil, 2013 National Health Survey - Stopa, Sheila Rizzato; Malta, Deborah Carvalho; Monteiro, Camila Nascimento; Szwarcwald, Célia Landmann; Goldbaum, Moisés; Cesar, Chester Luiz Galvão (Revista de saúde pública, 2017)
ABSTRACT OBJECTIVE To analyze the use of health services in the Brazilian population by sociodemographic factors, according to data from the 2013 Brazilian National Health Survey. METHODS The study analyzed data from 205,000 Brazilian citizens in all age groups who participated in the Brazilian National Health Survey, a cross-sectional study carried out in 2013. Prevalence and confidence intervals were estimated for indicators related to access to and use of health services according to age group, level of education of head of household, and Brazilian macroregions. RESULTS Among individuals who sought health services in the two weeks prior to the survey, 95.3% (95%CI 94.9–95.8) received care in their first visit. Percentages were higher in the following groups: 60 years of age and over; head of household with complete tertiary education; living in the South and Southeast regions. In addition, 82.5% (95%CI 81.2–83.7) of individuals who received health care and prescriptions were able to obtain all the necessary medicines, 1/3 of them from SUS. Less than half the Brazilian population (44.4%; 95%CI 43.8–45.1) visited a dentist in the 12 months prior to the survey, with smaller percentages among the following groups: 60 years of age or older; head of household with no education or up to incomplete elementary; living in the North region of Brazil. CONCLUSIONS People living in the South and Southeast regions still have greater access to health services, as do those whose head of household has a higher level of education. The (re)formulation of health policies to reduce disparities should consider differences encountered between regions and social levels. RESUMO OBJETIVO Descrever o uso de serviços de saúde na população brasileira segundo fatores sociodemográficos, de acordo com dados da Pesquisa Nacional de Saúde, 2013. MÉTODOS Foram analisados dados referentes a 205 mil brasileiros, de todas as faixas etárias, que participaram da Pesquisa Nacional de Saúde, estudo transversal conduzido em 2013. Calcularam-se as prevalências e seus intervalos de confiança para indicadores referentes ao acesso e a utilização dos serviços de saúde, segundo grupos de idade, nível de instrução do chefe da família e macrorregiões do país. RESULTADOS Dentre os indivíduos que procuraram o serviço de saúde nas duas semanas prévias à pesquisa, 95,3% (IC95% 94,9–95,8) conseguiu usá-lo na primeira vez que procurou. As proporções foram maiores: no grupo de 60 anos ou mais; cujo chefe da família tinha nível superior completo; e nas regiões Sul e Sudeste. Ainda, dos indivíduos atendidos e que tiveram medicamentos receitados, 82,5% (IC95% 81,2–83,7) conseguiram obter todos os medicamentos, sendo 1/3 pelo SUS. Menos da metade da população brasileira (44,4%; IC95% 43,8–45,1) consultou um dentista nos 12 meses anteriores à pesquisa, com proporções menores entre: indivíduos com 60 anos ou mais; cujo chefe da família não possuía nível de instrução ou tinha até o fundamental incompleto; e indivíduos que residiam na região Norte do país. CONCLUSÕES Pessoas que residem nas regiões Sul e Sudeste ainda possuem maior acesso aos serviços de saúde, bem como aquelas cujo chefe da família tem maior nível de instrução. A (re)formulação de políticas de saúde no intuito de reduzir disparidades deve considerar as diferenças regionais e entre níveis sociais encontradas.